Infectious Clones of Tomato Chlorosis Virus: Toward Increasing Efficiency by Introducing the Hepatitis Delta Virus Ribozyme - Navas-Hermosilla, Elisa; Fiallo-Olivé, Elvira; Navas-Castillo, Jesús (Frontiers in Microbiology, 2021)
Tomato chlorosis virus (ToCV) is an emergent plant pathogen that causes a yellow leaf disorder in tomato and other solanaceous crops. ToCV is a positive-sense, single stranded (ss)RNA bipartite virus with long and flexuous virions belonging to the genus Crininivirus (family Closteroviridae). ToCV is phloem-limited, transmissible by whiteflies, and causes symptoms of interveinal chlorosis, bronzing, and necrosis in the lower leaves of tomato accompanied by a decline in vigor and reduction in fruit yield. The availability of infectious virus clones is a valuable tool for reverse genetic studies that has been long been hampered in the case of closterovirids due to their genome size and complexity. Here, attempts were made to improve the infectivity of the available agroinfectious cDNA ToCV clones (isolate AT80/99-IC from Spain) by adding the hepatitis delta virus (HDV) ribozyme fused to the 3′ end of both genome components, RNA1 and RNA2. The inclusion of the ribozyme generated a viral progeny with RNA1 3′ ends more similar to that present in the clone used for agroinoculation. Nevertheless, the obtained clones were not able to infect tomato plants by direct agroinoculation, like the original clones. However, the infectivity of the clones carrying the HDV ribozyme in Nicotiana benthamiana plants increased, on average, by two-fold compared with the previously available clones.